AN ALGORITHMIC STRATEGY FOR FINDING CHARACTERISTIC MAPS OVER WEDGED SIMPLICIAL COMPLEXES - Choi, Suyoung; Vallée, Mathieu (Pacific Journal of Mathematics, 2022)
The puzzle method was introduced by Choi and Park as an effective method for finding nonsingular characteristic maps over wedged simplicial complexes K( J) obtained from a given simplicial complex K. We study further the mod 2 case of the puzzle method. We firstly describe it completely in terms of linear algebraic language which allows us to develop a constructive puzzle algorithm. We also analyze our algorithm and compare its performances with other known algorithms including the Garrison and Scott algorithm.
Keywords: Algorithmic strategy; Characteristic map; Puzzle algorithm; Puzzle method; Small covers; Toric topology; Wedge operation; Wedged simplicial complex